Neonatal Intraventricular Hemorrhage: Risk Factors and Clinical Outcome - Jouni, Oday (Latakia University Journal -Medical Sciences Series, 2019)
Intraventricular hemorrhage(IVH) is one of the most important problems in the early neonatal period , and an important cause of morbidity and mortality in very and extremely low birth weight infants, which can lead to long-term neurological consequences such as cerebral palsy, lack of psychomotor development and convulsions. This study was the first to be conducted at the Tishreen University Hospitals, highlighted the risk factors and clinical outcome of IVH in newborns ,under the conditions of work of neonatal intensive care unit at Tishreen University Hospital.During the years 2017-2018. The number of admissions registered in the neonatal intensive care unit of Tishreen University Hospital was 1159, IVH was diagnosed in 46 neonates(3.96%). 86.95% of cases recorded in preterm infants. The two severe degrees of IVH (III, IV) accounted for 50% of total study sample . 67.39% of IVH cases were diagnosed in very and extremely low birth weight infants. Most IVH cases (60,86%) occurred during the first three days of life , 67,85% of these were recorded in very and extremely low birth weight infants. Respiratory distress syndrome was recorded for 52,17% of all neonates in the study sample , IVH accured in 73.91% of neonates with artificial ventilation , prior to or concurrent with haemorrhage. Pathologic acidosis was recorded in 54,34% of the study sample . Sodium bicarbonate was infused to 36,95% of the sample and hyperglycemia was reported in 34,78% of the study population . The sex pattern of the neontes was not related to IVH , as well as to the type of delivery.Three deaths (9.09%) occurred in neonates with IVH - II , while 88.23 % of neonates suffered from IVH-III and all neonate of IVH-IV had died. Hydrocephaly was recorded at all survivors of the IVH-III. Full recovery was recorded in only 7 cases(21.21%) ,all of which were IVH-II . We excluded IVH-I from the clinical outcome, because this degree usually develops properly and leaves no sequels. Conclusion: degrees III and IV accounted for half of the cases of IVH in newborns, who are subjected to intensive care unite in the division of premature and newborn Diseases at the Tishreen University Hospital , mostly recorded in very and extremely low birth weight infants during the first three days of life, respiratory distress syndrome was the most important risk factors for its occurrence. يعتبر النزف داخل البطينات الدماغية من أهم المشاكل المرضية في مرحلة الوليد الباكرة ,وسببا هاما للمراضة والوفيات عند الخدج شديدي وفائقي نقص وزن الولادة , وهو يمكن ان يقود الى عقابيل عصبية طويلة الأمد كاستسقاء الدماغ والشلل الدماغي ونقص التطور الروحي الحركي والاختلاجات .تأتي أهمبة هذه الدراسة من كونها الأولى التي تجرى في المشافي الجامعية التابعة لجامعة تشرين والتي تم من خلالها تسليط الضوء على كل من عوامل الخطورة والسير السريري للنزف داخل البطينات الدماغية عند حديثي الولادة ضمن ظروف عمل شعبة أمراض الخديج والوليد في مشفى تشرين الجامعي بلغ عدد القبولات المسجلة في شعبة الخديج والوليد في مشفى تشرين الجامعي ,خلال العامين (2017-2018), 1159قبولاﹰ.شخص النزف داخل البطينات الدماغية عند 46 وليداﹰ(3,96%), معظمها ( 86,95%) كان قد سجل عند الخدج . شكلت الدرجتان الشديدتان من النزف داخل البطينات الدماغية(III,IV) 50% من مجمل حالات النزف , مع العلم أن 67,39 % من حالات النزف داخل البطينات الدماغية كانت قد شخصت عند شديدي وفائقي نقص وزن الولادة . حدثت معظم حالات النزف داخل البطينات الدماغية (60,86%) خلال الثلاثة أيام الأولى للحياة , 67,85% منها سجلت عند الخدج شديدي وفائقي نقص وزن الولادة . تعرض 52,17 % من مجموع حالات النزف داخل البطينات الدماغية لتناذر الشدة التنفسية, خضع ,73,91 % من ولدان عينة الدراسة للتهوية الاصطناعية قبل حدوث النزف أو بالتزامن مع حدوثه . سجل الحماض المرضي عند 54,34% , وكان هناك تسريب لبيكربونات الصوديوم عند 36,95% من مجموع ولدان عينة الدراسة . سجل فرط سكر الدم عند 34,78% من حالات النزف داخل البطينات الدماغية . لم يكن لجنس المولود علاقة مع حدوث النزف داخل البطينات الدماغية وكذلك لطريقة الولادة . سجلت ثلاث حالات وفاة(9,09%) عند الولدان بنزف بطينات درجة ثانية , بينما حدثت الوفاة عند 88,23 % من الولدان بنزف بطينات درجة ثالثة وعند جميع الولدان بنزف بطينات درجة رابعة . سجل استسقاء الدماغ عند كل من تبقى على قيد الحياة من مجموعة النزف درجة ثالثة . سجل الشفاء التام في 7 حالات فقط (21,21%),جميعهم كانوا من مجموعة النزف درجة ثانية , مع العلم اننا استثنينا حالات النزف درجة I من حسابات فقرة السير السريري لان هذه الدرجة عادة تتطور بشكل سليم ولاتترك عقابيل.من خلال ماسبق يمكن أن نستنتج أن الدرجتين IIIوIV كانتا قد شكلتا نصف حالات النزف داخل البطينات الدماغية عند حديثي الولادة ,الخاضعين لظروف العناية المشددة في شعبة أمراض الخديج والوليد في مشفى تشربن الجامعي , معظمها سجل عند الخدج شديدي وفائقي نقص وزن الولادة وشخصت خلال الأيام الثلاثة الأولى للحياة , كان تناذر الشدة التنفسية من أهم عوامل الخطورة لحدوث النزف .